2019
DOI: 10.3390/rs11050498
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Experiment for the Statistical Evaluation of Aerosol Retrieval (STEAR) Algorithms

Abstract: We have developed a method for evaluating the fidelity of the Aerosol Robotic Network (AERONET) retrieval algorithms by mimicking atmospheric extinction and radiance measurements in a laboratory experiment. This enables radiometric retrievals that use the same sampling volumes, relative humidities, and particle size ranges as observed by other in situ instrumentation in the experiment. We use three Cavity Attenuated Phase Shift (CAPS) monitors for extinction and University of Maryland Baltimore County’s (UMBC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 100 publications
0
32
0
Order By: Relevance
“…The development of the GRASP algorithm is described in Dubovik et al (2011Dubovik et al ( , 2014, and a description of some PARASOL/GRASP aerosol products can be found in Chen et al (2018), Kokhanovsky et al (2015), Popp et al (2016) and Sayer et al (2018). The accuracy of the GRASP algorithm configured for AERONET measurements has been evaluated with a laboratory experiment by Schuster et al (2019).…”
Section: Polder/parasol Aerosol Dataset Generated By the Grasp Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the GRASP algorithm is described in Dubovik et al (2011Dubovik et al ( , 2014, and a description of some PARASOL/GRASP aerosol products can be found in Chen et al (2018), Kokhanovsky et al (2015), Popp et al (2016) and Sayer et al (2018). The accuracy of the GRASP algorithm configured for AERONET measurements has been evaluated with a laboratory experiment by Schuster et al (2019).…”
Section: Polder/parasol Aerosol Dataset Generated By the Grasp Algorithmmentioning
confidence: 99%
“…We should note that AERONET aerosol datasets are averaged of all available data during the daytime (lunar photometer aerosol products will probably be available in the future; e.g., Barreto et al, 2016, andBerkoff et al, 2011) and that the GEOS-Chem daily aerosol properties are averaged based upon daytime and nighttime simulations. Additionally, the use of AERONET data comparing against corresponding 2 • × 2.5 • grid box model simulation could bring some sampling issues that cannot be ignored (Schutgens et al, 2016). Figure 6 shows the comparison of a priori (red) and a posteriori (blue) GEOS-Chem model simulated AOD, AAOD, SSA, AExp and AAExp with the AERONET dataset.…”
Section: Comparison With Aeronet Measurementsmentioning
confidence: 99%
“…GRASP first demonstrated its overall capability in an aerosol retrieval test study (Kokhanovsky et al, 2010). It has gone on to prove itself in a variety of real-world applications (Chen et al, 2018(Chen et al, , 2019Frouin et al, 2019;Li et al, 2019;Schuster et al, 2019;Torres et al, 2017). GRASP has been successfully applied to measurements from many different types of instruments (Benavent-Oltra et al, 2019;Espinosa et al, 2017Espinosa et al, , 2018Román et al, 2018;Titos et al, 2019;Torres et al, 2017), but the most pertinent to AirHARP are the previous applications of GRASP to POLDER-3 on PARASOL (Chen et al, 2018(Chen et al, , 2019Dubovik et al, 2011;Frouin et al, 2019;Li et al, 2019) because of its familiar polarization, multi-wavelength, and multi-angle sampling characteristics.…”
Section: Generalized Retrieval Of Aerosol and Surface Properties (Grasp)mentioning
confidence: 99%
“…In addition, a careful understanding of aerosol properties is essential for air quality monitoring/mitigation, characterizing fertilization of ecosystems, hydrological forecasting, etc. (Shiraiwa et al, 2017;Westberry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al (2017) demonstrated the high potential of GRASP retrieval concept for inverting only direct Sun photometric observations. Espinosa et al (2017Espinosa et al ( , 2019 and Schuster et al (2019) used GRASP approach for processing in situ aircraft and laboratory light scattering measurements. Most of these studies benefited from previous GRASP implementations and included certain new elements needed in specific applications.…”
Section: Application Of Grasp Concept To Lidar Data and Their Combinamentioning
confidence: 99%